Rock shelters in Slovenian Istria as a potential for the development of geotourism in the region - Ozis, Leni; Trpin, Jernej; Šmuc, Andrej (Geologija, 2014)
Geotourism is a special form of tourism which focuses on visiting geological and geomorphological sites. In the article we discuss the basic terms regarding geotourism, geodiversity and geoconservation, and then present the main features of rock shelters, i.e. landforms whose formation has not yet been elucidated. In our opinion rock shelters in Slovenian Istria have a potential to become sites for geotourism. We evaluated the geotourism potential of five rock shelter locations: Veli Badin, Štrkljevica, Mišja peč, Stena and Kavčič. The results of the evaluation show that three of the chosen rock shelter locations have a potential to develop as geotourist sites. Research confirmed our assumptions that the lack of scientific knowledge about rock shelters is a weakness from the geotourist point of view. Beside more detailed research on rock shelters, other activities, e.g. management of the sites, creating tourist activities, Information material etc. are also needed if we want rock shelters to become geotourist sites in the future.